2014
DOI: 10.1002/wrna.1227
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in skeletal muscle development, growth, atrophy, and disease

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs that are important global- as well as tissue- and cell-type-specific regulators of gene expression. Muscle-specific miRNAs or myomirs have been shown to control various processes in skeletal muscles, from myogenesis and muscle homeostasis to different responses to environmental stimuli, such as exercise. Importantly, myomirs are also involved in the development of muscle atrophy arising from aging, immobility, prolonged exposure to microgravity, or muscular and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 166 publications
(193 reference statements)
1
42
0
Order By: Relevance
“…Most of these appear to exert conserved roles across species and have functions from the early phases of myogenesis, from stem cell differentiation through to myofiber atrophy. Within these a subset commonly identified as myomiRs are highly expressed within skeletal muscle (Kovanda et al, 2014) and have reported roles in skeletal muscle maintenance processes (McCarthy, 2014a). We have identified a number of differences in miR expression between powerlifters and controls which through transcriptional regulation (Figure 6) may partially explain the divergent powerlifter phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these appear to exert conserved roles across species and have functions from the early phases of myogenesis, from stem cell differentiation through to myofiber atrophy. Within these a subset commonly identified as myomiRs are highly expressed within skeletal muscle (Kovanda et al, 2014) and have reported roles in skeletal muscle maintenance processes (McCarthy, 2014a). We have identified a number of differences in miR expression between powerlifters and controls which through transcriptional regulation (Figure 6) may partially explain the divergent powerlifter phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Here we will review miRNAs involved in glucose homeostasis and lipid metabolism in skeletal muscle, with an emphasis on metabolic disorders such as type 2 diabetes and the adaptive response to exercise training. Additionally we will raise some methodological considerations for studying miRNAs, as well as challenges investigators may A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 face when elucidating the direct role of miRNAs in the regulation of glucose and lipid metabolism in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest an important role for microRNAs (miRNAs) in skeletal muscle development and hypertrophy (for review see [4]), however, much less is known regarding miRNA regulation of glucose and lipid metabolism in skeletal muscle. In this respect, miRNAs may fine tune the expression of networks of genes that control glucose and lipid metabolism in health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are genetically conserved small non‐coding RNAs, containing about 22 nucleotides that post‐transcriptionally control gene expression. Skeletal muscle‐enriched microRNAs (myomiRs) play an important role in the regulation of muscle development, growth, regeneration, and metabolism . The microRNA‐1 and microRNA‐133a can regulate myogenesis by suppressing the predicted target gene histone deacetylase 4 (HDAC4), which upregulates myogenic markers as myocyte enhancer factor 2C (MEF2c), myogenic differentiation factor D (MyoD), and follistatin expression .…”
Section: Introductionmentioning
confidence: 99%